Generalized plasticity model for inelastic RCFT column response. (May 2016) - Kostic, Svetlana M.; Filippou, Filip C.; Deretic-Stojanovic, Biljana
Highlights: A nonlinear 3d concentrated plasticity element for RCFT column analysis is presented. The implemented return mapping algorithm is computationally very efficient. The calibration of model parameters for simulation of RCFT columns is discussed. The element accuracy is validated through correlation studies. Abstract: This paper presents a nonlinear 3d concentrated plasticity beam–column element for the analysis of RCFT columns. The element consists of a linear elastic component with a plastic hinge at each end whose inelastic response is described by extending the concept of generalized plasticity to stress resultants. With independent yield and limit surfaces it is possible to describe the gradual yielding of composite sections and their post-yield hardening behavior. The geometric nonlinearity under large displacements is accounted for with the corotational formulation. The paper discusses the calibration of the model parameters and assesses the accuracy of the model through correlation studies.